Modern Islamic Boarding School English Teachers’ Workload and Their Performance : A Phenomenological Analysis - Mohammad Umar Fakhrudin; Suwandi, Suwandi; Turini; Willy Eka Septian; Ramadhani, Aulia (EDUPEDIA Publisher, 2024)
A modern Islamic boarding school is increasingly becoming a popular choice for further education because it offers bilingual or multilingual programs. To effectively implement these programs, teachers need to be highly qualified, as they are required to manage three different curricula. This study aims to explore the impact of the workload on the teaching performance quality of Islamic boarding school teachers. A descriptive case study approach was used, and data were collected through interviews with two English teachers from an Islamic boarding school, along with the researchers' own experiences. The findings indicate that an excessive workload negatively impacts the quality of teachers' performance.